Prophylaxis in Hemophilia - Júlia Plentz Portich; Dayenne Catelli; Ebellins Tabares Calvache; Cristiane Seganfredo Weber; Daniel Sander Hoffmann; Guilherme Rasia Bosi; Leo Sekine; Lucia Mariano da Rocha Silla (Clinical and Biomedical Research, 2023)
Hemophilia is an inherited X-linked coagulopathy defined by a deficiency or abnormality in the clotting function of factor VIII (Hemophilia A) or factor IX (Hemophilia B). Prophylaxis – the regular administration of therapeutic products to maintain hemostasis and prevent bleeding – is the mainstream of treatment. Addressing the development and scientific evidence for administrating prophylaxis is the goal of this review. Prophylaxis is the therapeutic modality of choice for people with severe hemophilia, being considered, in principle, a lifelong treatment. It should have an early onset, ideally as a primary, or at least secondary. Even lifelong tertiary prophylaxis seems to offer benefit, although further studies are still lacking. Individualized strategies should lead to an optimization of the dilemma between better joint outcomes versus involved costs.